TREATMENT OF ANTERIOR CROSSBITE USING ORTHODONTIC REMOVABLE APLLIANCE (A CASE REPORT) - Novianty, Shella Indri; Salma, Nuris; Suhartono, Budi; Hutami, Islamy Rahma; Aditya, Grahita; Safangat, Muhamat Muhtar; Putranto, Rama (Jurnal Medali, 2025)
Background: The management of anterior crossbite, especially in non-growing patients, is a challenging yet crucial aspect of orthodontic treatment. Anterior crossbite, if left untreated, can lead to significant functional and aesthetic issues, including abnormal dental wear, TMD, and compromised facial aesthetic. The correction of this type of malocclusion is essential to prevent long-term complications. In a non-growing patient, fixed orthodontic appliances have historically been the recommended treatment option for anterior crossbite. However, the use of orthodontic removable appliances has number of benefits, including patient comfort, ease of maintenance, and removability for oral hygiene purposes. This treatment modality is particularly advantageous for patients who seek a less invasive and more flexible approach to managing their dental condition.Case Report: The patient was a 24-year-old woman with a crossbite of the maxillary left permanent central and lateral incisors. Upper acrylic removable appliance, with an expansion jackscrew, was used to correct the crossbite. The total active treatment time was 2 months. In that 2-months period, the orthodontic treatment was not yet complete, but it was already showing good results.Discussion: The application of orthodontic removable appliance with expansion screw has shown promising results in addressing the challenge in anterior crossbite treatment. One of the primary benefits of using expansion screw in orthodontic removable appliance is its ability to apply gradual and controlled expansion forces. This allows for the realignment of teeth without causing undue stress on the periodontal ligaments and surrounding structure.Conclusion: The treatment of anterior crossbite in non-growing patients using orthodontic removable appliance presents a viable and effective alternative to fixed appliances. The positive outcomes observed in this case underscore the potential of orthodontic removable appliance to address similar malocclusions in non-growing patients.